Mastering Oracle SQL and SQL*Plus - deHaan, Lex (Apress : Imprint: Apress, 2005)
This exceptional book explains fundamentals in detail, supported by realistic examples, while most other books on the market do not properly cover such basics. If you work with relational databases you need to understand the SQL language. And you will gain full competence to define, access, and manipulate data in an Oracle database, if you do so following this book's guidance. This book is fully compliant with the latest version of the ANSI SQL standard, and fully updated for the Oracle 10g database. Furthermore, this book is based on a popular Netherlands college textbook (currently in its third edition). And author Lex de Haan is vastly experienced with the Oracle database, and has 25 years of teaching experience. de Haan is also a member of the ANSI/ISO SQL standardization national body.